Mixing and compounding of polymers : theory and practice - Manas-Zloczower, Ica (Munich : Hanser, 2009)
'A book about the theory and practice of the mixing and compounding of polymers'--Provided by publisher
Includes bibliographical references and index
Keywords: Plastics -- Mixing